2013
DOI: 10.1016/j.surg.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

miR-335 and miR-363 regulation of neuroblastoma tumorigenesis and metastasis

Abstract: Background microRNA (miRNA) functions broadly as post-transcriptional regulators of gene expression, and disproportionate miRNAs can result in dysregulation of oncogenes in cancer cells. We have previously shown that gastrin-releasing peptide receptor (GRP-R) signaling regulates tumorigenicity of neuroblastoma cells. Here, we sought to characterize miRNA profile in GRP-R silenced neuroblastoma cells, and to determine the role of miRNAs on tumorigenicity and metastatic potential. Methods Human neuroblastoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…It has reported that miR-363 expression was downregulated in CD4 + T cells of patients with RA [11,12], and involved in the development of variety of cancer invasion, metastasis and tumorigenesis [27][28][29]. In this study, miR-363 expression was reduced in PBMCs and DCs of patients with RA compared to that of the healthy control, which were consistent with previous work.…”
Section: Discussionsupporting
confidence: 92%
“…It has reported that miR-363 expression was downregulated in CD4 + T cells of patients with RA [11,12], and involved in the development of variety of cancer invasion, metastasis and tumorigenesis [27][28][29]. In this study, miR-363 expression was reduced in PBMCs and DCs of patients with RA compared to that of the healthy control, which were consistent with previous work.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, miR-363 was reported to be repressed in head and neck squamous cell carcinoma tissues with lymph node metastasis and cell lines with increased invasive potential [49]. Ectopic expression of miR-363-3p decreased in vivo metastatic capacity of human neuroblastoma cells [56] and reversed the resistance of the breast cancer cell to the chemotherapeutic agent cisplatin [57]. Considering these findings and those of our own study, we suggest miR-363-3p as a strong candidate for establishment of stemness of CD133 high CSLCs.…”
Section: Discussionmentioning
confidence: 99%
“…The dys-regulation of miRNAs is a key mechanism involved in the pathogenesis of neuroblastoma, with several tumor suppressor miRNAs having been identified (Jian et al, 2012;Lynch et al, 2012;Chen et al, 2013;Qiao et al, 2013;). Here we determined that expression of miR-200a, another potential tumor suppressor in neuroblastoma, was significantly lower in tumors than that adjacent non-tumor tissue in our patient cohort.…”
Section: Discussionmentioning
confidence: 99%